Association of Oral Anticoagulants and Proton-Pump-Inhibitor Co-Therapy with Hospitalization for Upper Gastrointestinal Bleeding - Ray, Wayne A. (JAMA, 2018)
IMPORTANCE: Anticoagulant choice and proton pump inhibitor (PPI) co-therapy could affect risk of upper gastrointestinal bleeding, a frequent and potentially serious complication of oral anticoagulant treatment. OBJECTIVE: Compare upper gastrointestinal bleeding hospitalization incidence for individual anticoagulants without and with PPI co-therapy and determine variation according to underlying gastrointestinal bleeding risk. DESIGN, SETTING, AND PARTICIPANTS: Retrospective cohort study in Medicare patients between 1 January 2011 and 30 September 2015. EXPOSURES: Apixaban, dabigatran, rivaroxaban or warfarin treatment; PPI co-therapy; and gastrointestinal bleeding risk score encompassing patient characteristics, medication use, and comorbidity. MAIN OUTCOMES AND MEASURES: Upper gastrointestinal bleeding hospitalizations: adjusted incidence and risk difference (RD) per 10,000 person-years of anticoagulant treatment, incidence-rate-ratios (IRR). RESULTS: There were 1,643,123 patients with 1,713,183 new episodes of oral anticoagulant treatment (mean age 76.4 [std, 2.4] years, 56.1% female, 74.9% atrial fibrillation). During 754,389 treatment person-years without PPI co-therapy, the adjusted incidence of upper gastrointestinal bleeding hospitalizations (N=7,119) was 115 (95% confidence interval, 112–118) per 10,000 person-years. The incidence for rivaroxaban (1,278 hospitalizations/114,168 person-years) was 144 (136–152) per 10,000 person-years, significantly greater than that for apixaban (279/43,970, IRR=1.97 [1.73–2.25], RD=71 [59 to 83]), dabigatran (629/79,739, IRR=1.19 [1.08–1.32], RD=23 [11 to 36]) and warfarin (4,933/516,512, IRR=1.27 [1.19–1.35], RD=30 [20 to 41]). The incidence for apixaban was significantly lower than that for dabigatran (IRR=0.61 [0.52–0.70], RD=−48 [−61 to −34]) and warfarin (IRR=0.64 [0.57–0.73], RD=−40 [−50 to −31]). When anticoagulant treatment with PPI co-therapy (264,447 person-years) was compared to that without PPI co-therapy, risk of upper gastrointestinal bleeding hospitalizations (N=2,245) was lower for each anticoagulant: apixaban—IRR=0.66 (0.52–0.85), RD=−24 (−38 to −11); dabigatran--IRR=0.49 (0.41–0.59), RD=−61 (−75 to −47); rivaroxaban:--IR=0.75 (0.68–0.84), RD=−36 (−49 to −22); warfarin—IRR=0.65 (0.62–0.69), RD=−39 (−44 to −34). Absolute differences between anticoagulants and treatment without/with PPI co-therapy were greater for patients with higher gastrointestinal bleeding risk scores. For patients in the upper quartile, the incidence for rivaroxaban without PPI was 327 (302–355) per 10,000 versus 120 (93–153) per 10,000 for apixaban with PPI (RD=208 [169 to 247]). CONCLUSIONS AND RELEVANCE: Among Medicare patients initiating oral anticoagulant treatment, incidence of upper gastrointestinal bleeding hospitalization was highest for rivaroxaban and lowest for apixaban and for each anticoagulant, was lower among patients prescribed PPI co-therapy. These findings may inform assessment of risks and benefits when choosing anticoagulant agents.